2014
DOI: 10.1371/journal.pone.0099653
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis and Conformational Transitions of the Cell Penetrating Peptide Transportan 10 in the Membrane-Bound State

Abstract: Structure analysis of the cell-penetrating peptide transportan 10 (TP10) revealed an exemplary range of different conformations in the membrane-bound state. The bipartite peptide (derived N-terminally from galanin and C-terminally from mastoparan) was found to exhibit prominent characteristics of (i) amphiphilic α-helices, (ii) intrinsically disordered peptides, as well as (iii) β-pleated amyloid fibrils, and these conformational states become interconverted as a function of concentration. We used a complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 97 publications
0
41
0
Order By: Relevance
“…Third, a deletion of a residue in the amphipathic segment has an effect of changing the amino acid register on the helical wheel, interspersing the hydrophobic and hydrophilic side chains. Several studies have shown that such mutations can alter the structure and/or topology of the peptides [58]. Based on these considerations, we anticipate that the naturally occurring PLN mutations at Arg9 to a hydrophobic residue may have a similar effect, with the regulatory cytoplasmic domain of the R9X mutants exhibiting altered dynamics relative to the wild type.…”
Section: Discussionmentioning
confidence: 93%
“…Third, a deletion of a residue in the amphipathic segment has an effect of changing the amino acid register on the helical wheel, interspersing the hydrophobic and hydrophilic side chains. Several studies have shown that such mutations can alter the structure and/or topology of the peptides [58]. Based on these considerations, we anticipate that the naturally occurring PLN mutations at Arg9 to a hydrophobic residue may have a similar effect, with the regulatory cytoplasmic domain of the R9X mutants exhibiting altered dynamics relative to the wild type.…”
Section: Discussionmentioning
confidence: 93%
“…Like all the other 9 existing SRCD beamlines worldwide, UV-CD12 has a standard experimental setup for static liquidstate experiments on proteins/peptides/nucleic acids, which is the basic equipment for all structural biology related work. In addition, based on the specialized expertise at IBG-2 and long-term solid-state NMR experience in the structural characterization of membrane-active peptides and transmembrane proteins in macroscopically oriented lipid samples (Fanghä nel et al, 2014;Strandberg et al, 2013;Walther et al, 2010), a new in-house-built SR-OCD experimental station has been integrated. It is the only SR-OCD based setup worldwide for solid samples with automated rotational averaging and data acquisition, and it provides improved spectral data quality especially for unsaturated and long-chain lipid environments at wavelengths < 200 nm.…”
Section: Discussionmentioning
confidence: 99%
“…This can involve the formation of lipid domains, an increase of bilayer thickness and curvature, and even tubulation of lipid vesicles at high P:L ratios [57]. Similarly, circular dichroism spectra and simulations showed that transportan 10 is highly helical when bound to vesicles, and inserts its hydrophobic face into the bilayer[43,59,6264]. After insertion into synthetic lipid vesicles, transportan interacts with lipid phosphates causing lipid rearrangement and changes in local curvature in the bilayer[25,47].…”
Section: Cpps Are Interfacially Active Peptidesmentioning
confidence: 99%